Principal's Role in Academic Supervision: Fostering Discipline and Independence in Primary Education - Ratna Kusuma Ningrum; Nurul Mutmainah; Retno Susilowati; Soejono Soejono (Papanda Publisher, 2026)
Academic supervision is crucial for improving instructional quality and embedding character values like discipline, responsibility, and independence in elementary education. However, inconsistencies in student learning behaviors persist despite existing programs, highlighting gaps in supervision processes at local public schools. This qualitative descriptive study was conducted at State Elementary School 4 Kuwaran, involving the principal and teachers as participants. Data were collected via in-depth interviews, classroom observations, and document analysis. Analysis employed data reduction, display, and conclusion drawing, with triangulation for validity. Findings indicate systematic planning aligned supervision with character goals, collaborative implementation fostered reflective feedback, and follow-up through coaching enhanced teacher practices. Students showed improved discipline, cooperation, and independence. Supporting factors included leadership and commitment; inhibitors were time constraints and teacher readiness. These results align with instructional leadership theory, emphasizing reflective supervision for sustainable character integration. The study bridges knowledge gaps by detailing the supervision cycle, offering practical insights for Indonesian elementary schools while suggesting broader applications despite single-site limitations.